Lifetime extension and opex reduction by adapting the operational strategy of wind farms. Issue 1 (1st April 2022) - Loepelmann, P.; Fischer, B.
Abstract: The increasing complexity of the requirements for the operation of wind turbines challanges conventional operating strategies. If revenues are generated from the power exchange, it makes sense to react to price fluctuations during operation. How should such responses be designed? What are the implications for the profitability of wind farm projects from an owner's perspective? By carrying out a case study, this paper assesses connecting and disconnecting wind turbines depending on electricity prices using economic criteria. The results of the case study show that it is sensible to shut down turbines in economically unfavorable situations. Lost low revenues are recovered by future revenues over a significantly extended lifetime of the turbines, and the profitability of the project increases considerably.